Applications of cell-penetrating peptides in regulation of gene expression. - Järver, P; Langel, K; El-Andaloussi, S; Langel, U (2007)
CPPs (cell-penetrating peptides) can be defined as short peptides that are able to efficiently penetrate cellular lipid bilayers. Because of this remarkable feature, they are excellent candidates regarding alterations in gene expression. CPPs have been utilized in in vivo and in vitro experiments as delivery vectors for different bioactive cargoes. This review focuses on the experiments performed in recent years where CPPs have been used as vectors for multiple effectors of gene expression such as oligonucleotides for antisense, siRNA (small interfering RNA) and decoy dsDNA (double-stranded DNA) applications, and as transfection agents for plasmid delivery.